Strategies to make Cohousing affordable for seniors in Canada: An environmental scan - Pahwa, Manisha; De Melo, Kristen; Hamid, Marzan; Karim, Fairuz; Lok, Chloe; Van Der Wal, Alison (Prepared by the McMaster Research Shop for Hamilton Aging in Community, 2022)
Seniors comprise an increasing share of the Canadian population and face complex health, social, and economic needs in the aging journey. Cohousing is a form of community that can help ameliorate some of these challenges by providing its members with a blend of social support and autonomous living. However, conventional cohousing models typically require members to purchase their own unit and pay monthly fees. As a result, Cohousing is financially inaccessible to many individuals who do not have the capital to invest in their own unit or who do not have a sustained source of sufficient income to pay monthly fees. This report presents findings from an environmental scan of affordability strategies to make cohousing more financially accessible to seniors. We found four overarching strategies: 1) Raising capital; 2) Cost subsidies; 3) Property management or governance; and 4) Partnerships. These strategies, along with recommendations for our partner organizations, are described in detail.
Keywords: Hamilton, community-based research, cohousing, communal living, healthy aging, affordable housing